Synthetic studies towards the total synthesis of Zopfiellamide A / Nor Saliyana Jumali - Jumali, Nor Saliyana (Institute of Graduate Studies, UiTM, 2016)
In this study, Zopfiellamide A was chosen as a target molecule due to its unique structure and its pharmacological importance. The synthetic strategy moving towards the synthesis of Zopfiellamide A was divided accordingly based on the C-5 and C-3 substitution groups. The first approached was focused on the insertion of C-5 substituents of Zopfiellamide A which is the construction of the quaternary carbon bearing the hydroxyl, isopropyl and carboxylic acid linked via the methylene group at C-5 position of the pyrrolidinone ring. Therefore, the C-3 position of the pyrrolidinone ring was protected by a methyl group. Methyl acetoacetate was dialkylated, brominated and cyclised with methylamine to form the required lactam skeleton. The synthesis of C-5 substituents involved olefination, Michael addition, alkylation and mono-decarboxylation to give decarboxylated product 30, which is closest to the target molecule 12. There were two more steps left, which are α-hydroxylation and hydrolysis of ester. The overall yield of reaction was about 30%. Meanwhile, the C-acylation on C-3 was done by preparing the studied template of pyrrolidine-2,4-dione template 38, via condensation, dieckmann cyclisation and decarboxylation reaction…